Regional E-Government - some problems from Czech regions point of view - Jan Capek (European Regional Science Association (ERSA), 2004)
The e-government should start with electronic collaboration of governmental departments. Several services, like email, video conference, discussion forums, use of shared documents, etc. should be supported for assisting the efficient and productive collaboration of remote governmental departments. Since the functionality of the provided services is well known, no detailed description of each service phase is provided. The services for citizens are offered through so called governmental portals. The typical use of a governmental portal is to provide information to the citizens and to support several types of citizen–government transactions (e.g. issuing birth certificates, submitting tax forms, conducting electronic payments, etc.). These services open security requirements for an e-Government platform. Their compilation has been based on the security requirements derived for each independent service suite, for the Authentication processes
Keywords: 330